2020
DOI: 10.20473/vol6iss20192pp331-343
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Kegunaan, Kemudahan Penggunaan, Keamanan Dan Privasi Serta Kepercayaan Dalam Penggunaan Zakat Online: Dengan Pendekatan Tam

Abstract: This research aim to examine the effect of perception usefulness, ease of use,  security and privacy and trust on online zakat in Indonesian. The sample of this study is the Muslim community in Indonesian who have fulfilled the provisions to pay zakat as many as 31 respondents. The data use are primary data collected using a questionnaire through google form. Indicators of research variables are measured using differential semantic scales 1 to 7. This study proves that usefulness, security and privacy as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…Therefore, the application is likely to increase the ZISWAF revenue target. This supports the research conducted Davis (1989), Rouibah ( 2009) and Wong et al (2013), Wiharjo & Hendratmi (2020), Baskoro & Karmanto, 2020), Purwanto et al, (2021) that PU and PEoU have a significant effect on Intention. Attitude (ATT) is a factor in a studied person providing a positive or negative response to the assessment of something given.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, the application is likely to increase the ZISWAF revenue target. This supports the research conducted Davis (1989), Rouibah ( 2009) and Wong et al (2013), Wiharjo & Hendratmi (2020), Baskoro & Karmanto, 2020), Purwanto et al, (2021) that PU and PEoU have a significant effect on Intention. Attitude (ATT) is a factor in a studied person providing a positive or negative response to the assessment of something given.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of TPB, it can also be analyzed that the encouragement of ease in forming positive experiences increases the addiction to digital platforms in ZISWAF payments. This is in line with the process of people's interest in using halal products because the response of positive experiences of individuals on the use of halal products has the potential to create a habit of consuming them (Mohamed Omar et al 2012;Aziz et al 2015;Abdul Latiff et al 2016;S.-L. Wong, Hsu, and Chen 2018;Hasyim 2018;Hasyim and Nurohman 2021;Purwanto, Sulthon, and Wafirah 2021;Wiharjo and Hendratmi 2020).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Akan tetapi, kemudahan pembayaran zakat melalui zakat digital memiliki beberapa resiko seperti kebocoran data, yang dapat disebabkan oleh peretasan pihak internal, peretasan pihak eksternal, dan kebocoran data akibat sistem pada platform digital tidak aman (Aswandi et al, 2020). Penelitian dari (Bahana Wiharjo & Achsania Hendratmi, 2019) menyatakan bahwa semakin tinggi tingkat keamanan dan privasi layanan zakat digital maka semakin tinggi pula penggunaan dan minat zakat secara digital. Sehingga dengan adanya resiko tersebut terdapat kemungkinan masyarakat tidak memiliki minat terhadap bertransaksi zakat melalui platform zakat digital.…”
Section: Pendahuluanunclassified
“…Several studies have shown that the effectiveness of distribution in donations felt by donors has a positive effect in this case with the use of technology including the interest in paying zakat, infaq and alms online in Kuala Lumpur (Wiharjo & Hendratmi, 2019), regarding perceptions of the use of zakat, infaq and almsgiving online in Indonesia (Jamaludin et al, 2017), regarding muzzaki's decision to pay zakat, infaq and alms through fintech gopay (Ichwan, 2020), regarding individual interest in using fintech sharia paytren as a tool for donation payment transactions (Amalia, 2018), regarding millennial Muslim community's interest in donating using fintech platforms (Niswah et al, 2019b), regarding the use of fintech in donations (Usman, 2020), regarding the adoption of online ZIS payments by Generation Z (Oktavendi, 2021), researching interest in paying ZIS through BSI Mobile (Arwani & Wahdati, 2020), examines the perceptions of the millennial generation regarding zakat online (Lathifah, 2020), analyzing the website of the amil zakat foundation on the intention to pay zakat online using the TAM approach (Sukoraharjo et al, 2018), regarding the interest in adopting the waqf crowdfunding model (Mohd Thas Thaker et al, 2018), regarding the interest in using Go-Pay digital payment service in donating (Joan, 2019). Meanwhile, opposing research in this study includes examining the determinants of millennial generation interest in paying zakat, infaq and alms online (Sulaeman & Ninglasari, 2020), researching interest in paying zakat through the kitabisa.com platform (Astuti & Prijanto, 2021).…”
Section: Introductionmentioning
confidence: 99%